Zombies - Pipe, Jim, 1966- (New York : Bearport Pub., 2007)
Describes beliefs about and reports of zombies in various cultures throughout history, and briefly discusses depictions of zombies in movies.
Includes index.
6.6
3-6
Keywords: Zombies -- Juvenile literature; Zombies; Zombies